2018
DOI: 10.1111/anu.12836
|View full text |Cite
|
Sign up to set email alerts
|

The extracts ofAngelica sinensisinhibit lipid oxidation in fish erythrocytes and improve growth, digestive, absorptive and antioxidant capacity in juvenile Jian carp (Cyprinus carpiovar. Jian)

Abstract: The study explored the effects of ethyl ether extract, ethyl acetate extract (EAE), acetone extract, ethanol extract and aqueous extract of Angelica sinensis (EAs) and ethoxyquin (EQ) on lipid oxidation in erythrocytes and growth, digestive, absorptive and antioxidant capacity in carp (Cyprinus carpio var. Jian). The results indicated that EAs and EQ respectively at the concentrations of 0.5 and 0.25 mg/ml suppressed lipid oxidation by decreasing the generation of ROS and restoring the activities of antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…There are additional examples of erythrocyte models to study effects of antioxidants, feed ingredients on lipid oxidation in muscles. Hua-Tao et al (2019) investigated effects of extract of Angelica sinensis and ethoxyquin on lipid oxidation in erythrocytes and on growth, digestion, and absorptive and antioxidant capacity in carp muscle. The results indicated that Angelica sinensis extracts and ethoxyquin at concentrations of 0.5 and 0.25 mg/ml suppressed lipid oxidation by decreasing the generation of reactive oxygen species and restoring the activities of antioxidants in hydroxyl radical-treated erythrocytes.…”
Section: Erythrocytesmentioning
confidence: 99%
“…There are additional examples of erythrocyte models to study effects of antioxidants, feed ingredients on lipid oxidation in muscles. Hua-Tao et al (2019) investigated effects of extract of Angelica sinensis and ethoxyquin on lipid oxidation in erythrocytes and on growth, digestion, and absorptive and antioxidant capacity in carp muscle. The results indicated that Angelica sinensis extracts and ethoxyquin at concentrations of 0.5 and 0.25 mg/ml suppressed lipid oxidation by decreasing the generation of reactive oxygen species and restoring the activities of antioxidants in hydroxyl radical-treated erythrocytes.…”
Section: Erythrocytesmentioning
confidence: 99%
“…Accumulation of free radicals in tissue can result in chronic diseases associated with cancer, cardiovascular disease, diabetes and arthritis. It has been reported that some of the ethnomedicinal plants such as Cinnamon zeylanicum , Andrographis paniculata , Eugenia polyantha , Curcuma xanthorrhiza , Angelica sinensis and Orthosiphon stamineus are proven to fight various illnesses ranging from a common fever to metabolic disease in Asian regions 65,66 . Herbal plants contain a considerable amount of antimicrobial substances potentially utilised as herbal medications to fight a wide range of pathogenic microbes 67 .…”
Section: Beneficial Effects Of Medicinal Plants In Aquaculturementioning
confidence: 99%
“…It has been reported that some of the ethnomedicinal plants such as Cinnamon zeylanicum, Andrographis paniculata, Eugenia polyantha, Curcuma xanthorrhiza, Angelica sinensis and Orthosiphon stamineus are proven to fight various illnesses ranging from a common fever to metabolic disease in Asian regions. 65,66 Herbal plants contain a considerable amount of antimicrobial substances potentially utilised as herbal medications to fight a wide range of pathogenic microbes. 67 Different plants contain considerable bioactive compounds, including steroids, proteins, tannins, saponins, terpenoids and alkaloids.…”
Section: B Enefi Cial Effec Ts Of Med I Cinal Pl Ants In Aquaculturementioning
confidence: 99%